Montelukast Use Decreases Cardiovascular Events in Asthmatics - Hoxha, Malvina; Tedesco, Calogero C.; Quaglin, Silvana; Malaj, Visar; Pustina, Linda; Capra, Valerie; Evans, Jilly F.; Sala, Angelo; Rovati, G. Enrico (Frontiers in Pharmacology, 2021)
Cysteinyl leukotrienes are pro-inflammatory mediators with a clinically established role in asthma and a potential human genetic and preclinical role in cardiovascular diseases. Given that cardiovascular disease has a critical inflammatory component, the aim of this work was to conduct an observational study to verify whether the use of a leukotriene antagonist may protect asthmatic patients from a major cardiovascular event and, therefore, represents an innovative therapy to target inflammation in cardiovascular prevention. We performed an observational retrospective (three years) study on eight hundred asthmatic patients 18 years or older in Albania, equally classified in two cohorts, exposed or non-exposed to montelukast, matched by age and gender. Patients with a previous history of myocardial infarction or ischemic stroke were excluded. Overall 37 (4.6%) of the asthmatic patients, 32 non-exposed and 5 exposed, suffered a major cardiovascular event during the 3 years observation period. All the cardiovascular events occurred among patients with an increased cardiovascular risk. Our analyses demonstrate that exposure to montelukast remained a significant protective factor for incident ischemic events (HR = 0.222; HR = 0.241, respectively), independently from gender. The event-free Kaplan-Meier survival curves confirmed the lower cardiovascular incidence of patients exposed to montelukast. Collectively, our data indicates that there is a potential protective role of montelukast for incident ischemic events in the older asthmatic population, suggesting a co-morbidity benefit of montelukast in asthmatics and possible innovative therapy to target inflammation for cardiovascular prevention.